Arabidopsis WRKY57 Functions as a Node of Convergence for Jasmonic Acid– and Auxin-Mediated Signaling in Jasmonic Acid–Induced Leaf Senescence. Issue 1 (14th January 2014) - Jiang, Yanjuan; Liang, Gang; Yang, Shizhuo; Yu, Diqiu
Abstract : This work demonstrates that WRKY57 functions in the crosstalk between jasmonic acid (JA)– and auxin-mediated signaling during JA-induced leaf senescence. The findings provide a mechanistic insight into how JA-induced leaf senescence is antagonized by auxin via WRKY57. Abstract: Leaf senescence is regulated by diverse developmental and environmental factors. Exogenous jasmonic acid (JA ) can induce leaf senescence, whereas auxin suppresses this physiological process. Crosstalk between JA and auxin signaling has been well studied, but not during JA -induced leaf senescence. Here, we found that upon methyl jasmonate treatment, Arabidopsis thaliana wrky57 mutants produced typical leaf senescence symptoms, such as yellowing leaves, low chlorophyll content, and high cell death rates. Further investigation suggested that senescence-associated genes were upregulated in the wrky57 mutants. Chromatin immunoprecipitation experiments revealed that WRKY57 directly binds to the promoters of SENESCENCE4 and SENESCENCE-ASSOCIATED GENE12 and represses their transcription. In vivo and in vitro experiments suggested that WRKY57 interacts with JASMONATE ZIM-DOMAIN4/8 (JAZ4/8) and the AUX/IAA protein IAA29, repressors of the JA and auxin signaling pathways, respectively. Consistent with the opposing functions of JA and auxin in JA -induced leaf senescence, JAZ4/8 and IAA29 also displayed opposite functions in JA -induced leaf senescence and competitively interacted with WRKY57. Our results suggested that the JA -induced leaf senescence process can be antagonized by auxin via WRKY57. Moreover, WRKY57 protein levels were downregulated by JA but upregulated by auxin. Therefore, as a repressor in JA -induced leaf senescence, WRKY57 is a common component of the JA - and auxin-mediated signaling pathways.